Iron quantification in basal ganglia: quantitative susceptibility mapping as a potential biomarker for Alzheimer’s disease – a systematic review and meta-analysis - Ghaderi, Sadegh; Mohammadi, Sana; Nezhad, Nahid Jashire; Karami, Shaghayegh; Sayehmiri, Fatemeh (Frontiers in Neuroscience, 2024)
Introduction: Alzheimer's disease (AD), characterized by distinctive pathologies such as amyloid-β plaques and tau tangles, also involves deregulation of iron homeostasis, which may accelerate neurodegeneration. This metaanalysis evaluated the use of quantitative susceptibility mapping (QSM) to detect iron accumulation in the deep gray matter (DGM) of the basal ganglia in AD, contributing to a better understanding of AD progression, and potentially leading to new diagnostic and therapeutic approaches. Methods: Using the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines, we systematically searched the PubMed, Scopus, Web of Sciences, and Google Scholar databases up to October 2023 for studies employing QSM in AD research. Eligibility criteria were based on the PECO framework, and we included studies assessing alterations in magnetic susceptibility indicative of iron accumulation in the DGM of patients with AD. After initial screening and quality assessment using the Newcastle-Ottawa Scale, a meta-analysis was conducted to compare iron levels between patients with AD and healthy controls using a random-effects model.The meta-analysis included nine studies comprising 267 patients with AD and 272 healthy controls (HCs). There were significantly higher QSM values, indicating greater iron deposition, in the putamen (standardized mean difference (SMD) = 1.23; 95% CI: 0.62 to 1.84; p=0.00), globus pallidus (SMD=0.79; 95% CI: 0.07 to 1.52; p=0.03), and caudate nucleus (SMD=0.72; 95% CI: 0.39 to 1.06; p=0.00) of AD patients compared to HCs. However, no significant differences were found in the thalamus (SMD=1.00; 95% CI: -0.42 to 2.43; p=0.17). The sensitivity analysis indicated that no single study impacted the overall results. Age was identified as a major contributor to heterogeneity across all basal ganglia nuclei in subgroup analysis. Older age (>69 years) and lower male percentage (≤30%) were associated with greater putamen iron increase in patients with AD. Conclusions: The study suggests that excessive iron deposition is linked to the basal ganglia in AD, especially the PUT. The study underscores the complex nature of AD pathology and the accumulation of iron, influenced by age, sex, and regional differences, necessitating further research for a comprehensive understanding.